Pengembangan Desain Pembelajaran Al-Qur'an dan Hadis untuk Meningkatkan Minat Belajar Peserta Didik Kelas VIII Madrasah Tsanawiyah An-Nur Padang Sidempuan - Anisa Oktaviana; Muhammad Alfiansyah; Nur Ainun Matauli Pohan; Asmalia Asmalia (Jurnal Dirosah Islamiyah, 2023)
Al-Qur'an and Hadith are guidelines for life for Muslims because they contain good values ​​that must be applied and studied, especially in educational institutions. This study aims to develop a learning design in the subject of Al-Qur'an and Hadith at Madrasah Tsanawiah An Nur Padang Sidimpuan. The method of collecting data in this study is to use a qualitative approach and use the case study method. Data collection techniques were carried out through interviews and field observations. The results of this study are increasing students' interest in the learning process by using innovative methods, the obstacles that occur during the learning process are caused by the difficulty of students understanding learning resources, namely Arabic text books, the need for high interpretation to understand learning resources, lack of facilities and supporting learning resources, and so on. The solution offered in this study is to involve students actively in the learning process and teachers are expected to be able to guide students during the learning process. Keywords: Learning Design, Development, Interest in Learning Al-Qur'an Hadith.